RELATIVE DOSING OF PHOSPHATE BINDERS FOR EFFECTIVE MANAGEMENT OF PHOSPHATE AND PROTEIN INTAKE IN CHRONIC KIDNEY DISEASE - J Brian Copley; Jamie Heise (The Korean Society of Nephrology, 2012)
Patients with chronic kidney disease undergoing haemodialysis have a maximum recommended dietary phosphate (P) intake of 1000 mg/day and a recommended protein intake of 1.2 g/kg/day. Achieving this level of protein intake is associated with the best patient outcomes. However, protein-containing foods also contain P, and elevated serum P is associated with increased all-cause mortality. It is therefore important to manage the levels of serum P while maintaining adequate levels of nutrition. For different P binders, we estimated the dose and associated tablet burden needed to remove excess P based on the maximum recommended daily P intake. We also examined the implications for patient nutrition. Published binding capacities of different P binders in healthy volunteers ingesting up to 2000 mg/day P, are in the range of 26-135 mg P/g binder. Assuming that 60% of ingested P is absorbed, and that haemodialysis three-times weekly will remove 2400 mg P, a haemodialysis patient ingesting 1000 mg/day P will have a residual P burden of 257 mg/day. To bind this, patients would require a maximum of 3 x 1000 mg lanthanum carbonate tablets, or approximately 9 x 400 mg calcium carbonate tablets, or approximately 9 x 800 mg sevelamer hydrochloride tablets. The recommended protein intake for a 70 kg haemodialysis patient is 84 g/day. A realistic estimate of the average P content of a typical diet is 15 mg/g protein, which equates to a P intake of 1260 mg/day. This is considerably in excess of the recommended limit and, depending on vitamin D status more than 60% may be absorbed, further adding to the residual P burden. The availability of binding capacity data for P binders, presents physicians with the possibility of tailoring doses of binder to a patient's diet, facilitating sufficient intake of dietary protein while maintaining a neutral P balance. Use of high-capacity binders, such as lanthanum carbonate, would minimize the tablet burden faced by patients and this may also encourage adherence.